Impact of physical fitness and exercise training on subcutaneous adipose tissue beiging markers in humans with and without diabetes and a high-fat diet-fed mouse model - Bódis, Kálmán Benedikt; Breuer, Saida; Crepzia-Pevzner, Assja; Zaharia, Oana-Patricia; Schön, Martin; Saatmann, Nina; Altenhofen, Delsi; Springer, Christian; Szendrödi, Julia; Wagner, Robert; Al-Hasani, Hadi; Roden, Michael; et al. (Diabetes, obesity and metabolism, 2023)
Abstract Aims Exercise training induces white adipose tissue (WAT) beiging and improves glucose homeostasis and mitochondrial function in rodents. This could be relevant for type 2 diabetes in humans, but the effect of physical fitness on beiging of subcutaneous WAT (scWAT) remains unclear. This translational study investigates if beiging of scWAT associates with physical fitness in healthy humans and recent-onset type 2 diabetes and if a voluntary running wheel intervention is sufficient to induce beiging in mice. Materials and Methods Gene expression levels of established beiging markers were measured in scWAT biopsies of humans with (n?=?28) or without type 2 diabetes (n?=?28), stratified by spiroergometry into low (L-FIT; n?=?14 each) and high physical fitness (H-FIT; n?=?14 each). High-fat diet-fed FVB/N mice underwent voluntary wheel running, treadmill training or no training (n?=?8 each group). Following the training intervention, mitochondrial respiration and content of scWAT were assessed by high-resolution respirometry and citrate synthase activity, respectively. Results Secreted CD137 antigen (Tnfrsf9/Cd137) expression was three-fold higher in glucose-tolerant H-FIT than in L-FIT, but not different between H-FIT and L-FIT with type 2 diabetes. In mice, both training modalities increased Cd137 expression and enhanced mitochondrial content without changing respiration in scWAT. Treadmill but not voluntary wheel running led to improved whole-body insulin sensitivity. Conclusions Higher physical fitness and different exercise interventions associated with higher gene expression levels of the beiging marker CD137 in healthy humans and mice on a high-fat diet. Humans with recent-onset type 2 diabetes show an impaired adipose tissue-specific response to physical activity.